Mesoamerican religions and archaeology - Bošković, Aleksandar. (Oxford)
viii, 91 sayfa
Keywords: “Our understanding of ancient Pre-Columbian civilizations has changed significantly as the result of archaeological research in the last fifty years. Major projects during this period included dealing with cultural change in different contexts (Valley of Mexico, Oaxaca), regional research projects (“Olmec”), as well as attempts to understand more general trends in interpreting Pre-Columbian art and ideology (Codex Cihuacoatl, Templo Mayor). This book presents both the changes that occurred in the last few decades, and the impact that they had on our understanding on ancient Mesoamerican religions and cultures. It also includes references to some lesser-known research traditions (such as Croatia, Serbia, and Slovenia), as well as to the work of scholars like Jacques Soustelle or Didier Boremanse. With the insistence on clear methodology, based on field research, this book uses the context of specific archaeological finds in order to put Pre-Columbian Mesoamerican cultures in a historical perspective. In terms of method, the author follows R. E. W. Adams, Jeremy Sabloff, Robert J. Sharer and other archaeologists in emphasizing the “field archaeology school” approach, with its insistence on using the data acquired in context. Archaeological and anthropological research is in itself fascinating enough to not need stolen artefacts, forged vases, fantastic stories and invented mythical genealogies. The main goal of this book is to produce a methodologically sound and ethically valid interdisciplinary introduction into the exciting world of ancient Mesoamerica.” --